2020
DOI: 10.1515/ijfe-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extrusion process parameters on specific mechanical energy and physical properties of high-moisture meat analog

Abstract: To investigate the effect of process parameters during high-moisture extrusion on system parameter (specific mechanical energy, SME) and product physical properties, blend of soy protein isolate, wheat gluten, and corn starch (50:40:10 w/w) was extruded using co-rotating twin screw extruder equipped with cooling die at 55 and 65% feed moisture, 150 and 170 °C barrel temperature, 150 and 200 rpm screw speed. The hardness and chewiness of products increased as all the extrusion process parameters became low. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
1
25
4
Order By: Relevance
“…Significant differences were observed in texturization index between FMC (p < 0.05) but not between SRS with significantly higher texturization indexes observed at 40% FMC than 50% and 60% (Table 4). These results contradict findings by Maung et al (2021) who found that the texturization index was significantly affected by SRS but not FMC. This discrepancy may not only be due to inherent differences between raw materials, but also due to the wide range of FMC tested in this study as Maung et al (2021) only tested narrow FMC ranges (55-65%).…”
Section: Texturization Indexcontrasting
confidence: 99%
“…Significant differences were observed in texturization index between FMC (p < 0.05) but not between SRS with significantly higher texturization indexes observed at 40% FMC than 50% and 60% (Table 4). These results contradict findings by Maung et al (2021) who found that the texturization index was significantly affected by SRS but not FMC. This discrepancy may not only be due to inherent differences between raw materials, but also due to the wide range of FMC tested in this study as Maung et al (2021) only tested narrow FMC ranges (55-65%).…”
Section: Texturization Indexcontrasting
confidence: 99%
“…The process allows production of fibrous structures starting from ingredients which would not have the ability to create a strong texture if using conventional devices and methodologies (52) . High-moisture extrusion can therefore contribute to the production of new 'analogue' food products, such as surimi (53,54) . Although these might be perceived by some as 'artificial', such foods can, if nutrient dense, contribute to a balanced and healthy diet, providing options for those who wish to reduce consumption of meat and fish.…”
Section: Food Processing: Friend or Foe?mentioning
confidence: 99%
“…Fish-meat is characterized by its fibrous gel structure and texture, where the techniques used to achieve this typical structure, in restructured fish products, have been previously divided into two strategies: bottom-up and top-down [ 6 , 34 , 35 ]. In the bottom-up strategy, the structural organization of a muscle-like structure is created gradually.…”
Section: Textural and Sensorial Properties Of Fishmentioning
confidence: 99%
“…In the top-down strategy, the three-dimensional structure is obtained by structuring of biopolymer blends using an external forcefield, facilitating the formation of an anisotropic structure [ 34 ]. Techniques among the first strategy are cultured meat production using tissue engineering, production of filamentous fungi, wet spinning and electrospinning, whereas among the second one are extrusion, freeze structuring and shear cell technology [ 34 , 35 ]. It should be noted, though, that the categories of bottom-up and top-down are not mutually exclusive, as most techniques involve both bottom-up and top-down elements.…”
Section: Textural and Sensorial Properties Of Fishmentioning
confidence: 99%